2003
DOI: 10.1063/1.1559430
|View full text |Cite
|
Sign up to set email alerts
|

Effect of illumination conditions on Czochralski-grown silicon solar cell degradation

Abstract: The substitutional B-interstitial O-related defects induced under an illumination, specific to B-doped Czochralski-grown silicon (Cz-Si), results in a solar cell efficiency loss of up to 3%. For a fundamental interpretation, the relationship between the solar cell performance and the minority-carrier lifetime degradation, and influence of the illumination conditions were investigated. A simulation of the cell performance degradation clearly represented that the degradation was explained as a result of the carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 8 publications
0
35
0
1
Order By: Relevance
“…. All measurements are performed at T = 303 ± 2 K As mentioned in the introduction other groups [11], [12] have commented that the measured decays can be difficult to fit with a single exponential decay and a double exponential function has therefore been used to fit the decay data. In this work we have found that for both the rapid and the slow decay, for all the investigated samples, a much better fit could be obtained if (10) is replaced by a rate equation of second order, so that…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…. All measurements are performed at T = 303 ± 2 K As mentioned in the introduction other groups [11], [12] have commented that the measured decays can be difficult to fit with a single exponential decay and a double exponential function has therefore been used to fit the decay data. In this work we have found that for both the rapid and the slow decay, for all the investigated samples, a much better fit could be obtained if (10) is replaced by a rate equation of second order, so that…”
Section: Resultsmentioning
confidence: 99%
“…In other work [11], [12] it has, however, been acknowledged that a satisfactory fit between this function and the measured decays is not always obtained. In these works a double exponential function has been used to fit the lifetime decay data.…”
mentioning
confidence: 99%
“…Several groups have studied the influence of varying illumination intensity on the B-O defect generation rate. These studies 9,10 have shown that the generation rate of the defect saturates at a certain illumination intensity. For highly degradable material, i.e., material with high concentrations of boron and oxygen, the defect generation rate saturates at about 1 mW/cm Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The laser beam was shaped and focused into a narrow line with a Gaussian half width of 50 6 5 lm. The incidence angle was set to 10 to avoid detection of the specular reflection from the laser beam by the charge-coupled device (CCD) camera. When the laser is turned on, the generated carriers will diffuse from the illuminated area into the adjacent area following the continuity equation.…”
mentioning
confidence: 99%
“…On the one hand, a quadratic dependence of the defect formation rate on the equilibrium hole concentration (p 0 ) was observed [24,27,28,94,128]. On the other hand, a dependence of the defect formation rate on the illumination intensity was also observed for low illumination intensities, up to approximately 0.01 suns, at which the reaction rate saturated [8,129]. This illumination intensity corresponds to a saturation of the electron dependence for the reaction with an excess electron concentration on the order of 1 × 10 11 cm −3 [130].…”
Section: Role Of Defect Formationmentioning
confidence: 80%